The pedagogical potential of virtual reality head-mounted displays in the training of pre-service history teachers to promote self-directed learning (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
The arrival of the Fourth Industrial Revolution (4IR) as well as the required and accompanying twenty-first century skills has led the educational system towards a position wherein significant methodological and pedagogical intervention is required in order to modernise the system to better accommodate the needs of the twenty-first century learner. Information and Communication Technologies (ICTs), such as Virtual Reality (VR) and its associated technologies, like Head-Mounted Displays (HMDs), have the potential to enhance the teaching and learning experiences of pre-service history teachers in virtual learning environments (VLEs). This article seeks to explore the pedagogical potential of VR-HMDs as ICT tools in the training of pre-service history teachers by affording them opportunities to engage with subject matter in VLEs such as a virtual Holocaust Museum, a WW II battle re-enactment and the Pearl Harbour attack. Concurrently, the paper sought to determine if VLEs could promote pre-service history teachers’ self-directed learning (SDL) skills through the allowance of these experience-based learning opportunities. The research for this study was conducted at a tertiary education institution within a classroom environment where pre-service history teachers made use of VR-HMDs to achieve specific history lesson objectives. Grounded in constructive and interpretive paradigms, the research further employed a single exploratory qualitative case study design with nonprobability purposive sampling and discourse analysis. To a lesser extent, quantitative data was also used, complementary to the qualitative data, in order to better understand the phenomena under investigation. Various data collection instruments, including questionnaires, worksheets, focus group interviews, and field notes, were used to gather data from the 15 pre-service history teachers as participants. The findings indicated that VR-HMDs and VLEs hold a significant positive potential for the teaching and learning of pre-service history teachers, as the advantages of this emerging technology far outweigh its disadvantages. Furthermore, the use of VR-HMDs in teaching fostered SDL skills such as goal setting, self-regulation, motivation, and critical thinking.
Keywords: Virtual reality (VR); virtual reality head mounted displays (VR-HMDs); virtual learning environments (VLEs); self-directed learning (SDL); pre-service history teachers; history teaching and learning